IMPACTS OF PRICE, PROMOTION AND GO FOOD CONSUMER SATISFACTION IN FACULTY OF ECONOMIC AND BUSINESS STUDENTS OF BHAYANGKARA UNIVERSITY SURABAYA - istanti, enny; sanusi, ruchan; GS, Achmad Daeng (Ekspektra : Jurnal Bisnis dan Manajemen, 2020)
In the current globalization era, global marketing is marketing that accepts complex (geocentric) world market similarities through the integration of domestic, foreign and international marketing activities that can create synergies while maintaining organizational strategic objectives and competitive advantage as the power of global marketing efforts. The existence of increasingly sophisticated information, transportation and communication technology is very supportive of the existence of global markets and closer distances and accelerating long periods of time. The target population in the study were students of the Faculty of Economics and Business, University of Bhayangkara Surabaya who had made purchases with a minimum of 2 times gofood. in this case the number of students of the Faculty of Economics and Business of the University of Bhayangkara Surabaya who had made purchases with a minimum of 2x gofood was 1083. So with the Slovin sample formula as many as 100 respondents. The variables in this study consisted of independent variables namely price, promotion, and discount, while the dependent variable was customer satisfaction. To find out the outcome simultaneously and partially used multiple linear regression analysis. The conclusion of this research is that there is a simultaneous and partial influence of prices, promotions and discounts on gofood consumer satisfaction among students of the Faculty of Economics and Business, Bhayangkara University, Surabaya. The dominant variable influencing consumer satisfaction is promotion.